Pengaruh Penghindaran Pajak pada Nilai Perusahaan dengan Kebijakan Hutang Sebagai Variabel Pemoderasi - Wanami P, Ni Wayan Sarasati Pramudia; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 27 No 1 (2019)DO - 10.24843/EJA.2019.v27.i01.p17, 2019)
Tax avoidance is one of the way to do the tax management, it can give a signal to the investors and make an impact to the firm value. The debt policy of a firm also can influence the investors’s assessment to the firm. This research has an objective to obtain empirical evidence about the impact of tax avoidance in firm value with debt policy as the moderating variabel. The research was conducted at manufactur company which listed in Indonesian Stock Exchange in 2013-2017 using purposive sampling method as sample selection method. The number of samples is 182 companies. Data analysis technique used is Moderated Regression Analysis (MRA). The result of this analysis is tax avoidance positively affect the firm value and the debt policy strengthen the impact of tax avoidance on the firm value. Keywords : Firm value, tax avoidance, debt policy